(untitled) (Journal of the College of Basic Education, 2022)
This study aimed at evaluating the use of faculty members at Al-Mustansiriya University. of the Internet in scientific research, and know the effect of each of the academic rank, gender, and experience in teaching. The sample of the study consisted of (267) faculty members, who were chosen in a stratified manner. randomly, and the researcher used a questionnaire consisting of three domains: the rate of use, its degree, and the extent of the diversity of this use. To answer the study questions, the arithmetic means and deviations were calculated. standard, percentages, and analysis